2011
DOI: 10.1007/s00018-011-0667-9
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic activity in cortical neurons under acute oxidative stress directly contributes to cell death

Abstract: Primary neurons undergo insult-dependent programmed cell death. We examined autophagy as a process contributing to cell death in cortical neurons after treatment with either hydrogen peroxide (H(2)O(2)) or staurosporine. Although caspase-9 activation and cleavage of procaspase-3 were significant following staurosporine treatment, neither was observed following H(2)O(2) treatment, indicating a non-apoptotic death. Autophagic activity increased rapidly with H(2)O(2), but slowly with staurosporine, as quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 61 publications
5
39
1
Order By: Relevance
“…However, it may inhibit the phosphorylation on Bcl2 family members to affect the level of these proteins. Moreover, STS induce more abundantly caspase-dependent apoptotic events in the primary cortical neurons (42). This can be part of the reason why the effect attributed to protein-protein interaction of Bcl2 family proteins is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may inhibit the phosphorylation on Bcl2 family members to affect the level of these proteins. Moreover, STS induce more abundantly caspase-dependent apoptotic events in the primary cortical neurons (42). This can be part of the reason why the effect attributed to protein-protein interaction of Bcl2 family proteins is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The major form of autophagy, macroautophagy, is a constitutive form of self-digestion that is activated by nutrient starvation, accumulation of misfolded proteins, or mTOR inhibition. Autophagy is an essential component of the stress response of cells (19,20); however, excessive autophagy can lead to cell death (21)(22)(23)(24). There is evidence that autophagy is impaired in Alzheimer disease (25), and inhibitors of mTOR such as rapamycin are reported to induce autophagic clearance of pathogenic proteins in neurodegenerative diseases (26,27).…”
Section: Bdnfmentioning
confidence: 99%
“…It was recently reported that H 2 O 2 induces autophagic cell death with elevated autophagic activity in primary cortical neurons. 57 However, it is reasonable to propose that enhanced autophagy could eliminate oxidized or damaged intracellular components as a cellular defense mechanism against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%